2000
DOI: 10.1159/000027720
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial Changes in Seasonal Allergic Rhinitis throughout the Year: Evidence of Coexistent Air Pollution and Local Secretory IgA Deficiency?

Abstract: To determine possible epithelial changes in seasonal allergic rhinitis, we examined epithelial cells in cytology swab preparations of 38 non-smoking patients, exclusively sensitized to grass pollen, throughout the year, and surgical material of 8 patients. Cytologically, we found a marked goblet cell hyperplasia during the period of grass pollen exposure, while meta- and dysplasia were found throughout the year. Immunohistochemically, a lack of secretroy IgA in the altered epithelium was detected. These result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
17
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 16 publications
4
17
0
Order By: Relevance
“…While this result was contrary to our original hypothesis, it should be noted that goblet cell hyperplasia is not a consistent feature of allergic rhinitis in people. A transient increase in intraepithelial mucosubstances has been noted in patients with allergic rhinitis following exposure to allergen [50,51]. In contrast, other studies found no change in nasal intraepithelial mucosubstances in allergic rhinitis patients [52,53].…”
Section: Discussionmentioning
confidence: 99%
“…While this result was contrary to our original hypothesis, it should be noted that goblet cell hyperplasia is not a consistent feature of allergic rhinitis in people. A transient increase in intraepithelial mucosubstances has been noted in patients with allergic rhinitis following exposure to allergen [50,51]. In contrast, other studies found no change in nasal intraepithelial mucosubstances in allergic rhinitis patients [52,53].…”
Section: Discussionmentioning
confidence: 99%
“…Epithelial damage is only minimal in the nasal mucosa of patients with allergic rhinitis (810)(811)(812). Moreover, epithelial cell metaplasia has been observed in the nasal biopsies of some patients suffering from perennial rhinitis (813,814).…”
Section: Allergic Inflammationmentioning
confidence: 99%
“…The established allergic sensitization against seasonal grass pollen of some subjects played a major role in this study. Since similar observations were made in a previous study [27] , a relation to the study medication could be ruled out.…”
Section: Discussionmentioning
confidence: 82%